2016
DOI: 10.3349/ymj.2016.57.2.449
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Korean Version of the DN4 Diagnostic Questionnaire for Neuropathic Pain in Patients with Lumbar or Lumbar-Radicular Pain

Abstract: PurposeTo evaluate the diagnostic value of the Korean version of the Douleur Neuropathique 4 (DN4) questionnaire and to validate this questionnaire in terms of psychometric properties in patients with chronic pain due to degenerative spinal disease.Materials and MethodsThe Korean version of the DN4 questionnaire, which was translated and linguistically validated by the MAPI Research Group, was tested on 83 patients with lumbar or lumbar-radicular pain. Test-retest reliability was evaluated in a subsample of 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
(55 reference statements)
2
17
3
Order By: Relevance
“…Against which newer tests can be compared”. There are studies regarding the validity of the DN4 using only one physician’s opinion[ 21 , 30 ]. To our opinion it is preferable to use two physicians as the gold standard, which is also performed in the original validation study of the DN4[ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Against which newer tests can be compared”. There are studies regarding the validity of the DN4 using only one physician’s opinion[ 21 , 30 ]. To our opinion it is preferable to use two physicians as the gold standard, which is also performed in the original validation study of the DN4[ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies also shown that only the self-completing part of the DN4 have demonstrated good discriminatory properties in identifying NeP. The DN4 questionnaire is cross-culturally adapted and validated in Arabic [ 13 ], Dutch [ 14 ], French [ 11 ], Greek [ 16 ], German [ 14 ], Hungarian [ 14 ], Italian [ 17 ], Korean [ 18 ], Persian [ 19 ], Portuguese [ 20 ], Spanish [ 21 ], Turkish [ 22 ], and Thai languages [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies also shown that only the self-completing part of the DN4 have demonstrated good discriminatory properties in identifying NeP. The DN4 questionnaire is cross-culturally adapted and validated in Arabic [13], Dutch [14], French [11], Greek [16], German [14], Hungarian [14], Italian [17], Korean [18], Persian [19], Portuguese [20], Spanish [21], Turkish [22], and Thai languages [23].…”
Section: Discussionmentioning
confidence: 99%